Mengukur Kinerja AI : Perbandingan Kepuasan Pengguna ChatGPT dan Google Gemini dalam Era Digital - Buana, Pratama Angga; Abriansah, Fausta Rizky; Kurniawan, Nanda Dwi; Ferdian, Praditya Rendi; Ma’arif, Daffa Nurin Nabil; Firdaus, Azmi Maulana (STMIK Sinar Nusantara, 2025)
This study aims to analyze user satisfaction with the artificial intelligence applications ChatGPT and Google Gemini using the End-User Computing Satisfaction (EUCS) method. This method evaluates five key dimensions: content, accuracy, format, ease of use, and timeliness. Data were collected from 78 respondents with diverse backgrounds using a Likert-based questionnaire. The results show that both applications fall into the